THE INFLUENCE OF THE SCHOOL ENVIRONMENT ON ACCOUNTING LEARNING OUTCOMES OF CLASS X STUDENTS ACCOUNTING SKILLS PROGRAM AT SMK NEGERI 1 PINRANG - Hadrianti, Siska; Idris, Hariany; Azis, Muhammad; Sahade, Sahade; Samsinar, Samsinar (Universitas Labuhanbatu, 2024)
This study aims to find out how much the school environment influences the accounting learning outcomes of class X students of the Accounting Expertise Program of SMK Negeri 1 Pinrang. The variables in this study are the school environment as an independent variable and learning outcomes as a bound variable. The population in this study is 101 students of Class X Accounting Expertise Program of SMK Negeri 1 Pinrang. The sampling technique uses a simple random sampling technique, so that the sample from this study is 50 students. The data collection techniques used are questionnaires and documentation. The data analysis techniques used are descriptive analysis of percentages, instrument tests, and hypothesis tests. Based on the results of the data analysis that has been carried out, the results of the descriptive analysis of the school environment were obtained of 86.12 percent which is classified as very high which means that the school environment has met the criteria to improve student learning outcomes, for learning outcomes obtained 81.26 percent which is classified as high which means that the average student accounting learning results are good and no students who get a score brought the minimum completeness that has been set. From the results of a simple linear regression analysis, the school environment Y = 54.515 + 0.318X which means that for every addition of one school environment value, the learning outcome value increases by 0.318 units. The results of the t-test obtained a significant value of 0.000 < 0.05 which means that the school environment has a significant effect on student learning outcomes, thus the hypothesis is accepted. Meanwhile, the results of the determination coefficient (r2) analysis obtained a value (r2) = 0.424 or 42 percent. This means that the school environment has a contribution or influence on learning outcomes of 42 percent, while the remaining 58 percent is influenced by other factors.Keywords : School Environment, Learning OutcomesAbstrak This study aims to find out how much the school environment influences the accounting learning outcomes of class X students of the Accounting Expertise Program of SMK Negeri 1 Pinrang. The variables in this study are the school environment as an independent variable and learning outcomes as a bound variable. The population in this study is 101 students of Class X Accounting Expertise Program of SMK Negeri 1 Pinrang. The sampling technique uses a simple random sampling technique, so that the sample from this study is 50 students. The data collection techniques used are questionnaires and documentation. The data analysis techniques used are descriptive analysis of percentages, instrument tests, and hypothesis tests. Based on the results of the data analysis that has been carried out, the results of the descriptive analysis of the school environment were obtained of 86.12 percent which is classified as very high which means that the school environment has met the criteria to improve student learning outcomes, for learning outcomes obtained 81.26 percent which is classified as high which means that the average student accounting learning results are good and no students who get a score brought the minimum completeness that has been set. From the results of a simple linear regression analysis,the school environment obtained Y = 54.515+ 0.318X, which means that for every additional value of the school environment, the learning outcome value increases by 0.318 units. The results of the t-test obtained a significant value of 0.000 <0.05, which means the school environment has a significant effect on student learning outcomes, thus the hypothesis is accepted. Meanwhile, the results of the analysis of the coefficient of determination (r2) obtained a value of (r2) = 0.424 or 42 percent. This means that the school environment has a contribution or influence on learning outcomes of 42 percent, while the remaining 58 percent is influenced by other factors.Keywords: School Environment, Learning Outcomes